2006
DOI: 10.1080/15459620500526552
|View full text |Cite
|
Sign up to set email alerts
|

Silica Exposure on Construction Sites: Results of an Exposure Monitoring Data Compilation Project

Abstract: To expand on the limited size and scope of construction silica exposure studies, a silica monitoring data compilation project was initiated through the American Conference of Governmental Industrial Hygienists Construction Committee. Personal silica exposure monitoring data was collected and analyzed from 13 private, research, and regulatory groups. An effort was made to collect as much detail as possible about task, tool, and environmental and control conditions so as much information as possible could be gar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 19 publications
2
47
2
Order By: Relevance
“…[18][19][20] However, the subgroup of workers best characterized in our study, including those engaged in stonework masonry and tunnel construction, can reasonably be considered at high risk for adverse health effects as a result of silica exposure based on their higher mean exposure level (AM50.057, 93% of exposure measurements above the ACGIH limit value). 12,13,18,21 It should also be noted that carpenters and joiners had significant mean RCS exposure levels (AM50.047, 93% of exposure measurements above the ACGIH limit value), comparable with those of miners and quarry workers (AM50.048, 97% of exposure measurements above the ACGIH limit value), likely reflecting an inadequate implementation of preventive measures to control workplace silica dust air concentrations in the Italian construction industry, similar to other economically developed countries. [19][20][21] We estimate that about 30 000 workers are exposed to crystalline silica in the manufacture of non-metallic minerals in Italy (NACE code 26) 12 Similarly, in our study, exposure levels in the manufacture of nonmetallic minerals were found to vary between and within occupations, leading to an overall mean concentration lower than in construction, as well as a smaller percentage of TLV overwhelming values.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…[18][19][20] However, the subgroup of workers best characterized in our study, including those engaged in stonework masonry and tunnel construction, can reasonably be considered at high risk for adverse health effects as a result of silica exposure based on their higher mean exposure level (AM50.057, 93% of exposure measurements above the ACGIH limit value). 12,13,18,21 It should also be noted that carpenters and joiners had significant mean RCS exposure levels (AM50.047, 93% of exposure measurements above the ACGIH limit value), comparable with those of miners and quarry workers (AM50.048, 97% of exposure measurements above the ACGIH limit value), likely reflecting an inadequate implementation of preventive measures to control workplace silica dust air concentrations in the Italian construction industry, similar to other economically developed countries. [19][20][21] We estimate that about 30 000 workers are exposed to crystalline silica in the manufacture of non-metallic minerals in Italy (NACE code 26) 12 Similarly, in our study, exposure levels in the manufacture of nonmetallic minerals were found to vary between and within occupations, leading to an overall mean concentration lower than in construction, as well as a smaller percentage of TLV overwhelming values.…”
Section: Discussionmentioning
confidence: 95%
“…12,13,18,21 It should also be noted that carpenters and joiners had significant mean RCS exposure levels (AM50.047, 93% of exposure measurements above the ACGIH limit value), comparable with those of miners and quarry workers (AM50.048, 97% of exposure measurements above the ACGIH limit value), likely reflecting an inadequate implementation of preventive measures to control workplace silica dust air concentrations in the Italian construction industry, similar to other economically developed countries. [19][20][21] We estimate that about 30 000 workers are exposed to crystalline silica in the manufacture of non-metallic minerals in Italy (NACE code 26) 12 Similarly, in our study, exposure levels in the manufacture of nonmetallic minerals were found to vary between and within occupations, leading to an overall mean concentration lower than in construction, as well as a smaller percentage of TLV overwhelming values. This may be due to the significant decrease of airborne RCS concentrations reported in the ceramic industry over time, 14,22 and to the high variation in whether workers use dry or automated/remotely controlled working methods.…”
Section: Discussionmentioning
confidence: 95%
“…Measured exposures to respirable dust in this study are moderate (GM ¼ 0.90 mg/m 3 , range ¼ 0.24-2.17 mg/m 3 ) compared with exposures in the construction industry [Linch et al, 1998;Lumens and Spee, 2001;Rappaport et al, 2003;Tjoe Nij et al, 2003;Flanagan et al, 2006].…”
Section: Discussionmentioning
confidence: 54%
“…Exposure levels in the construction industry still frequently exceed the limits [Flynn and Susi, 2003;Tjoe Nij et al, 2003;Flanagan et al, 2006]. Also, workers' behavior has been shown to be a relevant determinant of exposure [Lumens and Spee, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…Construction hazards have received considerable attention over the last two decades [5]. Researchers internationally have examined hazards, consequences, and costs and developed numerous interventions and tailored controls [6].…”
Section: Literature Reviewmentioning
confidence: 99%